Repositioning maneuvers in benign paroxysmal positional vertigo: how do we improve outcomes? - Banerjee, Tapas Kumar (International Journal of Research in Medical Sciences, 2021)
Benign paroxysmal positional vertigo (BPPV) is the most common peripheral vestibular disorder. A series of meetings with clinicians treating BPPV were conducted to seek their views on improving outcomes in patients with BPPV. BPPV is primarily treated by Otolith repositioning maneuvers (ORM) to help to move the otoconia out of the canal and lead it back to the vestibule. Although repositioning maneuvers are effective in BPPV management, some patients experience residual dizziness, postural instability, recurrences, and psycho-emotional consequences after about 1 month after repositioning. An important and useful non-pharmacological intervention for patients with balance disturbances is Vestibular rehabilitation (VR), which includes vestibular adaptation, habituation and substitution, and patient education. Repositioning devices and mastoid vibration could help a subgroup of patients with BPPV who do not respond to conventional management. Betahistine dihydrochloride accelerates the recovery of function of vestibular system by improving blood flow in the inner ear, and normalization of the function of motion sensitive hair cells is faster. Betahistine-treated patients may have faster recovery, lesser recurrence, and longer relief of symptoms. The use of betahistine in combination with maneuvers can help prevent the development of residual dizziness.